Venture creation patterns in academic entrepreneurship: the role of founder motivations - Stefan Hossinger; Jörn Block; Xiangyu Chen; Arndt Werner (The Journal of Technology Transfer, 2021)
The path to academic entrepreneurship is characterized by a sequence of venture creation activities, which can be classified into operational-, financing- and commercialization activities. Academic entrepreneurship research is concerned with the question how different motives of scientists affect the patterns of these venture creation activities. Using a longitudinal two-period dataset of 165 academic entrepreneurs from 73 universities in Germany, we propose and test a multi-activity-based model that links different types of entrepreneurial motives to venture creation activities. The findings show that founder motives related to self-realization, necessity and an increased financial income increase the likelihood of completing venture creation activities, whereas work-life balance motivations and the drive to make better use of one's professional knowledge decrease that likelihood. The desire to translate research ideas into practice has no effect. Our results further show that the positive effects of seeking self-realization and an increased financial income are more pronounced for completing commercialization activities than for operational activities. Our study contributes to research on academic entrepreneurship and entrepreneurial motivations and helps university administrators and policymakers to design their entrepreneurship support programs more effectively.
Keywords: 600; Academic entrepreneurship; Academic spin-offs; Motivation; Drivers; Venture creation patterns; M130; L260; O310; O320